2003
DOI: 10.1889/1.1832531
|View full text |Cite
|
Sign up to set email alerts
|

47.2: Plastic Displays ‐ Films for OLED Displays

Abstract: A plastic display will offer light weight construction, durability, and the potential for flexible product design. Key to achieving these goals is the design of the substrate. This paper will discuss the specifications of a plastic substrate for OLEDs, the development of a substrate that meets the processing requirements, and the results of device testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is currently considerable interest in flexible displays 1,2 and many electronic based companies currently are actively researching flexible displays based on primarily liquid crystal displays (LCD), [3][4][5] organic light emitting diodes (OLEDs) [6][7][8] and electrophoretic displays. 9 An example of a flexible OLED display is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently considerable interest in flexible displays 1,2 and many electronic based companies currently are actively researching flexible displays based on primarily liquid crystal displays (LCD), [3][4][5] organic light emitting diodes (OLEDs) [6][7][8] and electrophoretic displays. 9 An example of a flexible OLED display is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Innocenzo et al [18] reported on their research work with flexible OLEDs on PEN on DuPont display and their result indicated that the introduction of a smooth acrylic layer has efficiently improved the roughness values (≤ 0.02 µm) of the PEN substrates. In 2006, Hsu et al [12] fabricated a novel flexible OLED on PET by using a dot-nickel embedded ITO anode and improved the surface roughness values (from 2.60 nm to 0.36 nm) of the ITO anode.…”
Section: Introductionmentioning
confidence: 99%